Measuring procedure of experimental data acquisition and data evaluation of acoustic emission in rock disintegration - Lucia Ivaničová; Zuzana Chlebová; František Krepelka; Jozef Futó (Acta Montanistica Slovaca, 2009)
The paper describes the results of measurements of acoustic signal arising in rock disintegration on the drilling standof the Institute of Geotechnics SAS in Košice. The acoustic signal was registered with sonometer Mediator 2238. Registrationand processing of the acoustic signal is solved as a part of the research grant task within the basic research of the rock disintegrationby drilling.